Evaluation of Open-Pollinated and Hybrid Maize Varieties in the Spring Season at Baitadi District, Nepal (SAARC Journal of Agriculture, 2022)
Being a maize producing region, cultivation of hybrid and improved maize varieties in the spring season is very low in Baitadi district. In order to examine the performances of different maize varieties, five maize varieties including both open-pollinated (i.e. Arun-2, Arun-4 and Rampur composite) and hybrid varieties (i.e. Rajkumar and Rampur Hybrid-10) were tested using Randomized Complete Block Design (RCBD) in spring season during February to August, 2020 at Dasarathch and municipality-1, Baitadi. The highest days to emergence of seedlings was in Rampur Hybrid-10 (30 days) and the lowest days to emergence was in Arun-2 (23 days) and Arun-4 (23 days), respectively. The plant height was significantly higher in Rajkumar (156.4 cm), whereas the leaf area index were significantly higher in Arun-2 (4.36 cm). Similarly, the phenological behavior like days to 50% tasseling (112 days) and silking (119 days) were significantly earlier in Arun-4. Likewise, yield attributing characteristics like cob length, cob diameter, number of rows/cobs, number of kernels/rows, shelling%, thousand grain weight (TGW) were found significantly higher in hybrid maize varieties as compared to openpollinated varieties. Grain yield was found significantly higher in hybrids Rajkumar recording yield of 5.32 Mt ha-1 closely followed by Rampur Hybrid-10 (4.75 Mt ha-1) whereas open-pollinated Rampur composite, Arun-2 and Arun-4 recorded grain yield of 4.58 Mt ha-1, 3.99 Mt ha-1 and 2.33 Mt ha-1 respectively. The results indicated that hybrid varieties were promising and should be promoted for general cultivation in the hills area of Nepal.SAARC J. Agric., 19(2): 123-136 (2021)